Deep analysis of skin molecular heterogeneities and their significance on the precise treatment of patients with psoriasis - Zhang, Shengxiao; Chang, Minjing; Zheng, Leilei; Wang, Can; Zhao, Rong; Song, Shan; Hao, Jiawei; Zhang, Lecong; Wang, Caihong; Li, Xiaofeng (Frontiers in Immunology, 2024)
Psoriasis is a highly heterogeneous autoinflammatory disease. At present, heterogeneity in disease has not been adequately translated into concrete treatment options. Our aim was to develop and verify a new stratification scheme that identifies the heterogeneity of psoriasis by the integration of large-scale transcriptomic profiles, thereby identifying patient subtypes and providing personalized treatment options whenever possible. First, we identified 163 genes with differentially up-regulated expression in lesional skin using microarray datasets from lesional and non-lesional skin samples from 250 psoriatic patients. Subsequently, functional enrichment and network analysis were executed on these 163 genes, and three skin subtypes (A-C subtypes) were identified by unsupervised clustering. Among them, the immune cells and pathways related to inflammation were activated in subtype A, named immune activation. In contrast, subtype C, named stroma proliferation, exhibited a high level of stromal cells and signaling pathways that are associated with tissue proliferation. Subtype B was modestly activated in all the signaling pathways. Finally, an Xgboost classifier was utilized to predict the effects of methotrexate and commonly prescribed biologics on skin subtypes. Notably, subtypes A and B responded well to methotrexate and interleukin-12/23 inhibitors (ustekinumab), but not to tumor necrosis factor-α inhibitors and interleukin-17A receptor inhibitors.Contrastingly, subtype C had excellent results with tumor necrosis factor-α inhibitors (etanercept) and interleukin-17A receptor inhibitors (brodalumab) but not with methotrexate and interleukin-12/23 inhibitors. Thus, psoriasis patients can be assorted into three subtypes with different molecular and cellular characteristics based on the heterogeneity of the skin's immune cells and the stroma, determining the clinical responses of conventional therapies.